Effects of petrolatum, a petrolatum depositing body wash and a regular body wash on biomarkers and biophysical properties of the stratum corneum. (14th March 2021) - Wei, Karl; Stella, Ching; Wehmeyer, Kenneth; Christman, Jeremy; Altemeier, Amy; Spruell, Russell; Wimalasena, Rohan; Fadayel, Gina; Wickett, R. Randall
Abstract: Background: An important trend in the personal care industry involves the development of body wash products that not only clean the skin without damage but deposit conditioning ingredients to improve skin barrier function. Objective: The objective of this study was to develop skin biomarker measures to quantify the treatment effects of body wash products. Methods: We employed analysis of structural proteins (keratin 1, 10, 11 and involucrin), a natural moisturizing factor (pyrrolidone carboxylic acid) and an inflammatory mediator (IL‐1ra/IL‐1α) from adhesive discs with dry skin grading, TEWL and capacitance measurements to compare the effects of direct application of petrolatum, a high petrolatum depositing body wash, and a regular body wash on dry leg skin in a standard leg‐wash treatment protocol. Results: High depositing body wash and petrolatum had positive effects on stratum corneum barrier function as judged by biomarker analysis, biophysical measurements and skin grading compared to the regular body wash product. Conclusions: The results clearly indicate that a combination of biomarker and biophysical property measurements is effective for determining the skin benefits of moisturizing body wash products. Abstract : Résumé: Contexte: Une tendance importante dans l'industrie des soins personnels inclut le développement de produits de lavage corporel qui non seulement nettoient la peau sans l'endommager, mais déposent des ingrédients de traitement pour améliorer la fonction de la barrière cutanée. Objectif: L'objectif de cette étude était de développer des mesures de biomarqueurs cutanés permettant de quantifier les effets du traitement des produits de lavage corporel. Méthodes: Nous avons utilisé l'analyse de protéines structurelles (kératine 1, 10, 11 et involucrine), un facteur hydratant naturel (acide carboxylique de pyrrolidone) et un médiateur inflammatoire (IL‐1ra/IL‐1a) provenant de disques adhésifs avec cotation de la sécheresse cutanée, mesures de perte d'eau transépidermique (transepidermal water loss, TEWL) et de capacitance pour comparer les effets de l'application directe de vaseline, d'un produit de lavage corporel avec dépôt élevé de vaseline et d'un produit de lavage corporel ordinaire sur la peau sèche des jambes, dans un protocole de traitement de lavage des jambes standard. Résultats: Le produit de lavage corporel à dépôt élevé et la vaseline avaient des effets positifs sur la fonction de barrière de la couche cornée, comme évalué par l'analyse des biomarqueurs, les mesures biophysiques et la cotation de la peau, comparé au produit de lavage corporel ordinaire. Conclusions: Les résultats indiquent clairement qu'une combinaison de mesures des biomarqueurs et des propriétés biophysiques est efficace pour déterminer les bienfaits pour la peau des produits de lavage corporel hydratants.